MiR-204-5p mediates PERK inhibition to suppress growth and induce apoptosis in ovarian cancer through the eIF2α/ATF-4/CHOP pathway - Faranak Fallahian; Seyedeh Sara Ghorbanhosseini; Shekufe Rezghi Barez; Mahmoud Aghaei (Scientific Reports)
Abstract The unfolded protein response (UPR) is crucial in maintaining cell survival during stressful conditions, but prolonged ER stress can lead to apoptosis. Based on the evidence acquired, it has been suggested that inhibiting the protein kinase RNA-like ER kinase (PERK) pathway, which constitutes an adaptive branch of UPR, may represent a viable approach for impeding the proliferation of neoplastic cells. This study assesses the influence of PERK inhibition mediated by miR-204-5p on the growth of ovarian cancer cell lines, OVCAR3 and SKOV3. We demonstrated that miR-204-5p significantly downregulated the expression of PERK at the RNA and protein levels. The suppression of PERK, mediated by miR-204-5p, significantly diminished cellular viability and enhanced apoptotic cell death in cells exposed to Tunicamycin (Tm). We ascertained that the inhibition of PERK by miR-204-5p decreased eukaryotic initiation factor 2alpha (eIF2α) phosphorylation. Moreover, activating transcription factor 4 (ATF4) and CCAAT-enhancer-binding homologous protein (CHOP) expression levels were notably elevated in response to miR-204-5p. The expression of Bax and caspase-12 was found to be upregulated, while the expression of Bcl-2 was reduced. This study is the first to demonstrate that silencing the PERK gene through miR-204-5p significantly inhibits cell growth and promotes ER-stress-induced apoptosis in ovarian cancer cells.